SINERGI PENDIDIKAN, BUDAYA, DAN LINGKUNGAN SOSIAL DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI ERA GLOBALISASI - Mahdini; Rodhatul Jennah; Hamidah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This article examines the urgency of synergy among education, culture, and the social environment as a conceptual framework for shaping students’ character in the era of globalization, with the aim of analyzing the roles and integration of these three elements in strengthening character development that is contextual, sustainable, and aligned with societal dynamics. The study employs a qualitative approach using a literature review method, with data collected from various relevant sources, including books, scholarly journals, articles, and official documents related to the research theme. The collected data are analyzed systematically through stages of data collection, classification, and information processing, followed by drawing conclusions and data verification to obtain valid and in-depth findings. The results indicate that effective integration of education, culture, and the social environment plays a crucial role in shaping students’ character that is not solely oriented toward cognitive aspects, but also fosters moral values, cultural identity, social awareness, and environmental consciousness. Such synergy promotes a more contextual and applicable process of value internalization, enabling students to respond critically to global challenges without losing their grounding in local values and surrounding social realities.